Analisis Kepuasan Pelanggan Produk Abon Ikan di UMKM Babonsenyum dengan Metode SERVQUAL dan SWOT - Abdurrahman Juret; Yanuar Pandu Negoro; Hidayat Hidayat (Fakultas Teknik, 2023)
This study aims to analyze customer satisfaction as a foundation in designing marketing strategies for shredded fish products in Babonsenyum MSMEs. The methods used involve SERVQUAL (Service Quality) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). In the SERVQUAL method, service quality dimensions such as product reliability, speed of service, responsiveness to customers, communication, and physical aspects of the product are evaluated. The results of this method allow identifying gaps between customer expectations and perceptions of service, helping to improve the quality of products and services. Furthermore, the SWOT analysis identifies the internal strengths and weaknesses of Babonsenyum MSMEs as well as opportunities and threats from the external environment. Babonsenyum MSME customer satisfaction based on a perception value of 4.05, expectations of 4.38 with a positive gap value of 1.00 it can be seen that the expectation value exceeds the perception value with positive results. So it is felt that customer satisfaction is quite good. Recommendations for proposed improvements to improve supporting factors for customer satisfaction and company performance are to: Maintain product excellence in order to compete with similar competitors, maintain good relationships with raw material suppliers, maximize online sales so that other costs can be met. The results of these two methods help Babonsenyum MSMEs develop more effective marketing strategies and increase customer satisfaction, focusing on improving the quality of products, services, and utilizing existing opportunities.